Effects of PurePro Soy on Growth Performance and Fecal Dry Matter of Nursery Pigs - Jessica L. Smallfield; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt; Long Zou (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 360 barrows (DNA 200 × 400; initially 12.3 ± 0.05 lb) were used in a 37-d study to determine the effects of a refined soy protein concentrate (PurePro Soy, Bunge; Chesterfield, MO) on nursery-pig growth performance and fecal dry matter (DM). Pens of pigs were randomly allotted to one of six dietary treatments in a generalized randomized block design with BW as a blocking factor. There were six replications for each treatment within pens of light pigs (initially 11.0 ± 0.02 lb) and six replications for each treatment within pens of heavy pigs (initially 13.7 ± 0.02 lb). There were five pigs per pen and 12 pens per treatment. Diets were corn-soybean meal-based with increasing PurePro Soy (0, 4.25, 8.5, 12.75, and 17%) replacing SBM in the diet. A sixth diet served as a positive control containing 8.5% enzymatically treated SBM (HP 300, Hamlet Protein; Findlay, OH) also replacing SBM in the diet. Treatment diets were fed in two phases from d 0 to 9 (phase 1) and d 9 to 23 (phase 2) followed by a common diet from d 23 to 37 (phase 3). On d 9 and 23, fecal samples were collected from the same three randomly selected pigs in each pen to determine fecal DM. There were no interactions of treatment and BW block, therefore interpretation is focused on the main effect of treatment. During the experimental period (d 0 to 23), ADG and F/G improved (quadratic, P < 0.05) as PurePro Soy increased with the greatest improvement in ADG and F/G when PurePro Soy increased from 0 to 8.5%. Pigs fed 8.5% PurePro Soy or 8.5% HP 300 had similar performance. Additionally, ADFI increased (linear, P = 0.019) as PurePro Soy increased. Overall (d 0 to 37), increasing PurePro Soy improved (quadratic, P = 0.014) ADG and tended to worsen (linear, P = 0.087) F/G and increase ADFI (quadratic, P = 0.080) with the greatest response at 8.5%. For fecal DM, increasing PurePro Soy increased (linear, P = 0.035) fecal DM on d 9, and pigs fed 8.5% PurePro Soy had greater (P = 0.011) fecal DM than those fed 8.5% HP 300. In summary, replacing SBM with 8.5% PurePro Soy improved nursery pig growth performance and fecal DM.
Keywords: fecal dry matter; nursery pig; soy protein concentrate